AI-based audit acceptance and auditors’ technology readiness - Hamzah Al-Mawalia; Yaser Allozia; Aram Nawaiseha; Hala Zaidana; Abdul Rahman Al Natour; Muhammad Alshurideh (International Journal of Data and Network Science, 2025)
This study investigates auditors' willingness to adopt AI-based audit tools using the AI Device Use Acceptance (AIDUA) model, focusing on the factors influencing acceptance and the moderating role of technology readiness. Data were collected from 153 certified external auditors in Jordan, representing a 30% response rate. The findings reveal that social influence and hedonic motivation positively impact performance expectancy, while anthropomorphism influences effort expectancy. Emotions significantly affect auditors' willingness to adopt AI-based audits, moderated by their technology readiness. This study contributes to the literature by utilizing the AIDUA framework to understand AI acceptance in auditing, offering insights into the unique aspects of AI technologies. The results highlight the importance of understanding auditors' perceptions and readiness, providing valuable implications for practitioners and policymakers to develop strategies for effective AI integration in auditing. Future research should explore these dynamics in diverse cultural contexts and over extended periods to enhance the generalizability of the findings.